Sodium Butyrate Ameliorates Oxidative Stress-Induced Intestinal Epithelium Barrier Injury and Mitochondrial Damage through AMPK-Mitophagy Pathway. (29th January 2022) - Li, Xin; Wang, Chunchun; Zhu, Jiang; Lin, Qian; Yu, Minjie; Wen, Jiashu; Feng, Jie; Hu, Caihong
Abstract : Sodium butyrate has gained increasing attention for its vast beneficial effects. However, whether sodium butyrate could alleviate oxidative stress-induced intestinal dysfunction and mitochondrial damage of piglets and its underlying mechanism remains unclear. The present study used a hydrogen peroxide- (H2 O2 -) induced oxidative stress model to study whether sodium butyrate could alleviate oxidative stress, intestinal epithelium injury, and mitochondrial dysfunction of porcine intestinal epithelial cells (IPEC-J2) in AMPK-mitophagy-dependent pathway. The results indicated that sodium butyrate alleviated the H2 O2 -induced oxidative stress, decreased the level of reactive oxygen species (ROS), increased mitochondrial membrane potential (MMP), mitochondrial DNA (mtDNA), and mRNA expression of genes related to mitochondrial function, and inhibited the release of mitochondrial cytochrome c (Cyt c). Sodium butyrate reduced the protein expression of recombinant NLR family, pyrin domain-containing protein 3 (NLRP3) and fluorescein isothiocyanate dextran 4 kDa (FD4) permeability and increased transepithelial resistance (TER) and the protein expression of tight junction. Sodium butyrate increased the expression of light-chain-associated protein B (LC3B) and Beclin-1, reduced the expression of P62, and enhanced mitophagy. However, the use of AMPK inhibitor or mitophagy inhibitor weakened the protective effect of sodium butyrate on mitochondrial function and intestinal epithelium barrier function and suppressed the induction effect of sodium butyrate on mitophagy. In addition, we also found that after interference with AMPK α, the protective effect of sodium butyrate on IPEC-J2 cells treated with H2 O2 was suppressed, indicating that AMPK α is necessary for sodium butyrate to exert its protective effect. In summary, these results revealed that sodium butyrate induced mitophagy by activating AMPK, thereby alleviating oxidative stress, intestinal epithelium barrier injury, and mitochondrial dysfunction induced by H2 O2 .